Mindfulness, Loving-Kindness, and Compassion-Based Meditation Interventions and Adult Attachment Orientations: A Systematic Map - Taranah Gazder; Erica Ruby Drummond; Mine Gelegen; Sarah C. E. Stanton (Behavioral Sciences)
Meditation interventions have important benefits, including potentially helping those with higher attachment anxiety and avoidance enjoy better personal and relational growth. This preregistered and reproducible systematic map sought to identify the extent and scope of experimental evidence investigating the role of mindfulness, loving-kindness, and compassion-based multi-session meditation interventions in (a) moderating the effects of attachment orientations on outcomes over time and/or (b) changing attachment orientations over time. We conducted a systematic map, as the literature on meditation interventions and attachment is nascent. We searched 5 databases, screening 725 studies. We extracted data from four journal articles and one dissertation (five studies in total) which met our inclusion criteria. Four studies examined the effects of meditation interventions on buffering attachment insecurity and one examined attachment security enhancement. All five studies included a mindfulness meditation intervention, and one included a loving-kindness meditation intervention. All studies were conducted in Western cultures. Studies primarily found evidence for interventions benefitting those with higher attachment anxiety, although some evidence emerged for higher attachment avoidance. Our systematic map highlights a critical need for further application of meditation interventions in an attachment and personal growth context, given the promising nature of early work in this area.